Adenosine 3’:5’-Cyclic Monophosphate Induces Regulated Secretion of Tissue-Type Plasminogen Activator and von Willebrand Factor from Cultured Human Endothelial Cells - Hegeman, R. J.; Eijnden-Schrauwen, van den Y.; Emeis, J. J. (Thrombosis and Haemostasis, 1998)
The effect of compounds increasing intracellular adenosine 3’:5’-cyclic monophosphate [cAMP]i levels (prostacyclin, isoproterenol, forskolin, cholera toxin), and of the cAMP analogs 8-bromo-cAMP and dibutyryl-cAMP, on the regulated secretion (acute release) of tissue-type plasminogen activator (tPA) and von Willebrand factor (vWF) was studied in cultured human umbilical vein endothelial cells (HUVEC).Prostacyclin, isoproterenol and forskolin, which increased [cAMP]i in HUVEC, and the cell-permeant cAMP analog 8-bromo-cAMP induced dose- and time-dependent secretion of tPA and vWF. The extent of vWF and tPA release correlated with [cAMP]i, and was increased by the phosphodiesterase inhibitor isobutylmethylxanthine.In contrast to thrombin, the cAMP-elevating agents did not increase the intracellular calcium concentration [Ca2+]i in HUVEC. At sub-maximal concentrations, the effects of thrombin and prostacyclin were additive.Our results show that an increase in [cAMP]i resulted in regulated secretion (acute release) of tPA and vWF from HUVEC, without the concomitant increase in [Ca2+]i which is, in HUVEC, essential for thrombin-induced regulated secretion to occur. cAMP-induced secretion represents a novel mechanism for causing regulated secretion of tPA and vWF from endothelial cells.